2010
DOI: 10.1021/ja9097719
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and Reversible Mechanochromic Luminescence for Solid-State Difluoroboron Avobenzone

Abstract: Difluoroboron avobenzone (BF(2)AVB), a simple boron complex of a commercial sunscreen product, exhibits morphology-dependent emission and mechanochromic luminescence in the solid state. When scratched, smeared, or even gently touched, the emission color of BF(2)AVB films is significantly red-shifted under UV excitation. In the rubbed regions, the fluorescence recovers slowly at room temperature or much faster with heating, resulting in a simple rewritable "scratch the surface" ink of potential commercial use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
409
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 796 publications
(433 citation statements)
references
References 25 publications
16
409
0
1
Order By: Relevance
“…44 Accordingly, narrow-band and morphology-dependent fluorescence was observed. In particular, it was found that mechanochromic fluorescence was reversibly recovered even at room temperature.…”
Section: Mechanofluorochromic (Mfc) Materialsmentioning
confidence: 97%
“…44 Accordingly, narrow-band and morphology-dependent fluorescence was observed. In particular, it was found that mechanochromic fluorescence was reversibly recovered even at room temperature.…”
Section: Mechanofluorochromic (Mfc) Materialsmentioning
confidence: 97%
“…Among them, materials that exhibit reversible change in fluorescent color induced by mechanical stress such as grinding, namely "mechanofluorochromism", have recently been received attention. Several examples of both organometallic and pure organic materials have been reported to exhibit mechanofluorochromism [1][2][3][4][5][6][7][8][9][10][11][12][13] and these phenomena were generally believed to be due to change in intermolecular interactions caused by altering the molecular arrangements in the crystalline state by mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The subsequent reversion to their original luminescence colour is usually achieved upon recrystallization or thermal treatment. [1][2][3][4][5][9][10][11] These materials have attracted increased attention because of their potential 55 applications in optical storage and memories, mechanical sensors, displacement and deformation detectors, optoelectronic and display devices. 1 Such materials could also serve as models for studying the luminescent colour changes associated with structural changes of their molecular assemblies that switch from 60 one state to another under mechanical stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…36−44 Balch reviewed such visually detected changes in the luminescence of 10 gold and other transition metal complexes. 2 Fackler and coworkers reported that the grinding of the non-luminescent crystals of [(TPA) 2 Au][AuCN] (TPA = 1,3,5-triaza-7-phosphaadamantane) initiates a strong green emission.…”
Section: Introductionmentioning
confidence: 99%